ROTAVAC® does not interfere with the immune response to childhood vaccines in Indian infants: A randomized placebo controlled trial. Issue 5 (May 2017) - Chandola, Temsunaro Rongsen; Taneja, Sunita; Goyal, Nidhi; Antony, Kalpana; Bhatia, Kiran; More, Deepak; Bhandari, Nita; Cho, Iksung; Mohan, Krishna; Prasad, Sai; Harshavardhan, GVJA; Rao, Tataji Surender; et al.
Abstract: A phase III randomized double-blind placebo-controlled trial was conducted in the urban neighborhoods of Delhi to assess whether Oral Rotavirus Vaccine ROTAVAC ® interferes with the immune response to childhood vaccines when coadministered. Infants aged 6 weeks were randomized to receive three doses of either ROTAVAC ® or placebo along with childhood vaccines: Oral Polio Vaccine and vaccines against Diphtheria, Pertussis, Tetanus, Hepatitis B and Haemophilus influenza type b given as Pentavalent at 6, 10, 14 weeks of age. Blood specimens were collected from all infants at baseline and 4 weeks post dose 3 to assess the immune response to antigens in Oral Polio Vaccine, Pentavalent and ROTAVAC ® vaccines. Non-inferiority of immune response to all vaccine components of the childhood vaccines when ROTAVAC ® was administered concurrently was demonstrated. Non-inferior immune responses to childhood vaccines were evaluated based on the seroprotective levels of antibodies against polio types 1, 2, and 3, Diphtheria toxoid, Tetanus toxoid, Haemophilus influenza type b anti- polyribosyl ribitol phosphate antibodies and Hepatitis B antibodies; and the Geometric Mean Concentration for Pertussis. The proportion of infants who seroconverted (≥4 fold rise) was 38.6% in the ROTAVAC ® group and 12.2% in the placebo group. The frequency and severity of immediate adverse events, adverse events and serious adverse events were similar in both groups. None of the five reported deaths were considered to be related to the ROTAVAC ® and no case of intussusception meeting Brighton Diagnostic Certainty Level I criteria was reported. This study demonstrated that ROTAVAC ® can be safely administered with childhood vaccines without interfering with the immune response to the antigens contained in these vaccines.